Cost-effectiveness analysis of gumarontinib versus savolitinib for the treatment of advanced or metastatic NSCLC with MET exon 14 skipping mutations in China using partitioned survival model - Fang, Gang; Pi, Zhipeng; An, Yiping; Cao, Xinxin; Li, Wei; Zhu, Xiangjun; Ding, Jinxi (Frontiers in Pharmacology, 2025)
Background and objectivesBoth gumarontinib and savolitinib have demonstrated efficacy in treating non-small-cell lung cancer (NSCLC) with tumors harboring mesenchymal–epithelial transition factor gene exon 14 (METex14) skipping. However, the comparison of their efficacy and pharmacoeconomics profiles remains limited. This study aims to evaluate the cost-effectiveness of gumarontinib versus savolitinib for the treatment of METex14 skipping NSCLC in China.MethodsA 3-state partitioned survival model (PSM) was developed with lifetime horizon from the perspective of Chinese healthcare system. Survival inputs were based on an unanchored matching-adjusted indirect comparison using individual patient data from GLORY trial to adjust for patient characteristics in NCT02897479. Costs and outcomes were discounted at an annual rate of 5%. Sensitivity and scenario analyses were conducted to explore model uncertainty.ResultsGumarontinib gained an additional 0.10 QALYs at an incremental cost of $1,893 compared to savolitinib, resulting in the ICERs of $19,243/QALY, which is below the threshold of 3 times the GDP per capita in China ($35,007 per capita in 2022). Sensitivity and scenario analyses confirmed the robustness of the base-case results.ConclusionGumarontinib is a cost-effective option compared to savolitinib for METex14 skipping NSCLC in China.